2022
DOI: 10.1088/1742-6596/2240/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation substitutions in Y-type Ba0.5Sr1.5Me2Fe12O22 hexaferrites on the magnetic phase transitions

Abstract: We investigated the magnetic properties and magnetic phase transition in Y-type Ba0.5Sr1.5NiMgFe12O22 hexaferrite powder prepared by citrate sol-gel spontaneous combustion. The saturation magnetisation value of 32 emu/g at 4.2 K was lowered to 24 emu/g at 300 K. The magnetisations curves did not saturate even at a magnetic field of 50 kOe for both temperatures - 4.2 K and 300 K. A step-like behaviour appeared in the initial magnetisation curve at 4.2 K. A magnetic phase transformation from a spiral magnetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…These result from occurring metamagnetic transitions and to intermediate phases with different conical magnetic moments ordering in the crystal lattice. A similar step-like behavior was reported in ref for Ba 0.5 Sr 1.5 NiMgFe 12 O 22 powders also at 4.2 K. In ref , magnetic phase transitions were reported at 1.9 kOe, 8.5 kOe, and 20 kOe, corresponding to three ferroelectric phases and one ferromagnetic phase with collinear spins above 20 kOe in BaSrCoZnFe 11 O 22 polycrystalline samples at 200 K. In ref , a step-like behavior was registered in the initial magnetization curves of polycrystalline Ba 0.5 Sr 1.5 Zn 2– x Mg x Fe 12 O 22 samples ( x = 0–2), indicating that the increasing magnetic field induces intermediate magnetic phases ranging from conical ferromagnetic to proper screw spin orderings. The authors further observed an analogous magnetization curve variation for polycrystalline samples of Ba 0.5 Sr 1.5 Zn 2– x Mg x Fe 11 AlO 22 , but for x ≥ 0.8.…”
Section: Magnetic Phase Transitionssupporting
confidence: 83%
See 2 more Smart Citations
“…These result from occurring metamagnetic transitions and to intermediate phases with different conical magnetic moments ordering in the crystal lattice. A similar step-like behavior was reported in ref for Ba 0.5 Sr 1.5 NiMgFe 12 O 22 powders also at 4.2 K. In ref , magnetic phase transitions were reported at 1.9 kOe, 8.5 kOe, and 20 kOe, corresponding to three ferroelectric phases and one ferromagnetic phase with collinear spins above 20 kOe in BaSrCoZnFe 11 O 22 polycrystalline samples at 200 K. In ref , a step-like behavior was registered in the initial magnetization curves of polycrystalline Ba 0.5 Sr 1.5 Zn 2– x Mg x Fe 12 O 22 samples ( x = 0–2), indicating that the increasing magnetic field induces intermediate magnetic phases ranging from conical ferromagnetic to proper screw spin orderings. The authors further observed an analogous magnetization curve variation for polycrystalline samples of Ba 0.5 Sr 1.5 Zn 2– x Mg x Fe 11 AlO 22 , but for x ≥ 0.8.…”
Section: Magnetic Phase Transitionssupporting
confidence: 83%
“…As it is in the range of weak magnetic fields, this could be related to a ferrimagnetic and a helical ordering of spins. Such a behavior was again observed for Ba 0.5 Sr 1.5 Zn 0.5 Ni 1.5 Fe 11.92 Al 0.08 O 22 and Ba 0.5 Sr 1.5 NiMgFe 12 O 22 powders. It is well-known that in Ba 2– x Sr x Zn 2 Fe 12 O 22 , substituting Sr 2+ at x = 1.5 causes a magnetic phase change from a ferromagnetic Fe 3+ spin order in the nonsubstituted samples to a screw spin ordering. , Once impacted by a weak magnetic field, the magnetic system experiences transformations via metamagnetic states, including such between screw spin ordering and conical spin ordering.…”
Section: Magnetic Properties Of Y-hexaferritesmentioning
confidence: 99%
See 1 more Smart Citation